2009
DOI: 10.1002/hon.888
|View full text |Cite
|
Sign up to set email alerts
|

CD26 expression in mature B‐cell neoplasia: its possible role as a new prognostic marker in B‐CLL

Abstract: CD26 (dipeptidyl peptidase IV, DPP IV) is widely expressed by T and natural killer (NK) cells, epithelial and endothelial cells of different tissues, and it is strongly upregulated in activated B-cells; moreover it plays a regulatory role in the neoplastic transformation and progression of various types of tumours. CD26 expression was evaluated by means of flow cytometry in various peripheral B-cell lymphoid tumours: 12 follicular and 12 mantle cell lymphomas, 20 multiple myelomas (MMs), 12 hairy cell leukaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
39
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 39 publications
(49 reference statements)
15
39
1
1
Order By: Relevance
“…Interaction between B cells and T h cells in lymph node proliferating centres is mediated via CD40 crosslinking with CD40L to activate protein kinases such as Lyn and Syk and such interactions have been observed in CLL patient lymph nodes (28). The fact that CD26 was increased in surviving CLL cells is indicative of B-cell activation (29,30), which is consistent with the upregulation of CD58, another marker of costimulation. It has been shown that incubation of CLL cells with human CD40L-expressing T cells results in increased CD54, CD58, CD80, and CD86 (31).…”
Section: Discussionsupporting
confidence: 59%
“…Interaction between B cells and T h cells in lymph node proliferating centres is mediated via CD40 crosslinking with CD40L to activate protein kinases such as Lyn and Syk and such interactions have been observed in CLL patient lymph nodes (28). The fact that CD26 was increased in surviving CLL cells is indicative of B-cell activation (29,30), which is consistent with the upregulation of CD58, another marker of costimulation. It has been shown that incubation of CLL cells with human CD40L-expressing T cells results in increased CD54, CD58, CD80, and CD86 (31).…”
Section: Discussionsupporting
confidence: 59%
“…For example, both Dpp4 upregulation and Sell downregulation reportedly correlate with poor prognosis in human CLL, 44,45 which is consistent with the earlier onset of disease observed in DTG mice relative to Em-TCL1 mice. However, we cannot exclude the possible contribution of T cells in accelerating disease progression in DTG mice because T cells have been implicated in CLL development in Em-TCL1 mice, 46,47 and splenic T cells in DTG mice are quantitatively elevated compared with both dnRAG1 and Em-TCL1 mice at 36 weeks.…”
supporting
confidence: 72%
“…This is in part contradictory to a number of published studies. [48][49][50] The microarray study of Klein et al identified high CD26 expression as being associated with an un-mutated IgVH mutational status (5.6-fold upregulation compared to mutated CLL cases) (n = 16). Although no further validation or discussion of this finding was undertaken in their study, their finding corresponds to the recent study of Cro et al who also found high CD26 expression (>10% CD26 positive cells, identical to the cut-off used in this study) to be associated with an un-mutated IgVH mutational status and high CD49d expression in a study of 112 CLL patients.…”
Section: Discussionmentioning
confidence: 99%